Evaluasi Penerimaan Sistem E-Konseling Universitas Jambi Menggunakan Metode UTAUT3 - Sindy Nabila Indriani; Reni Aryani; Dewi Lestari (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
This thesis evaluates the acceptance of the E-counseling system at the University of Jambi using the Unified Theory of Acceptance and Use of Technology 3 (UTAUT 3) model. This research is based on the problem of mental health levels in students supported by data from WHO and the Ministry of Health. The University of Jambi provides online counseling services to help students solve their problems, but from the pre-research it was found that the level of knowledge and use of E-counseling is still very low. This study aims to implement the UTAUT 3 model which is used to identify factors that influence the acceptance of E-counseling at the University of Jambi. This study took a sample of 100 respondents from all active undergraduate students at the University of Jambi. The analysis technique used in this study is PLS-SEM (Partial Last Structural Equation Modeling) which uses the SmartPLS 4 application in its data calculation. The results obtained from the data calculation show that there are 4 hypotheses that have a significant influence, namely Habit on Use Behavior, Personal Innovativeness on Behavioral Intention, Hedonic Motivation on Behavioral Intention, and Facilitating Conditions on Use Behavior and 8 other hypotheses that do not have a significant influence, namely Performance Expectancy on Behavioral Intention, Effort Expectancy on Behavioral Intention, Social Influence on Behavioral Intention, Facilitating Condition on Behavioral Intention, Price Value on Behavioral Intention, Habit on Behavioral Intention, Personal Innovativeness on Use Behavior and Behavioral Intention on Use Behavior.